Analisis Faktor Adopsi Paylater Dengan Model UTAUT2 Pada Masyarakat DI Yogyakarta: Analysis of Factors Influencing Paylater Adoption Using the Unified Theory of Acceptance and Use of Technology 2 Model - Aulia Tirta Marshanda; Izzatun Nisa'; Alex Fahrur Riza (FAKULTAS EKONOMI DAN BISNIS ISLAM, 2026)
Purpose: analyze the factors influencing the adoption of paylater services among the community in the Special Region of Yogyakarta (DIY) by utilizing the Unified Theory of Acceptance and Use of Technology 2 (UTAUT2) framework. Design/methodology/approach: This research employs a quantitative approach with a survey method. Data were collected from 170 respondents in DIY using a purposive sampling technique. Data analysis was conducted using Structural Equation Modeling-Partial Least Squares (SEM-PLS) via SmartPLS 3 software, which includes the evaluation of the outer model and the inner model. Research Findings: indicate that Effort Expectancy, Social Influence, and Habit have a significant positive effect on the Behavioral Intention to use paylater services. Conversely, Performance Expectancy, Facilitating Conditions, Hedonic Motivation, and Price Value do not show a significant influence. Contribution/Originality/Novelty: contributes to the literature regarding financial technology adoption, specifically paylater services, with a focused scope on the Special Region of Yogyakarta